PENELITIAN NYALI DI TAMAN NASIONAL GUNUNG GEDE PANGRANGO DAN TAMAN NASIONAL GUNUNG HALIMUN SALAK, JAWA BARAT, INDONESIA [Research on gall in Mount Gede Pangrango and Mount Halimun Salak National Parks, West Java, Indonesia] - Rachman, Erlin; Tihurua, Eka Fatmawati; Sunaryo, Sunaryo (BERITA BIOLOGI, 2014)
Research on gall (including field and laboratory observations and field collecting) have been conducted in the Mounts Gede Pangrano (MGPNP) and Halimun Salak National Parks (MHSNP). This research focused on gall shapes, host plant species, and parts of the host plants infected by galls. The result showed that there were 169 gall numbers in MGNP and 127 numbers in MHSNP have been collected. Distribution of plant species infected by the galls were rather same in the both conservation areas. In MHSNP seven families mostly infected by galls: Araceae, 4 species of 5 gall numbers collection in the family (=4/5), Elaeocarpaceae (5/5), Euphorbiaceae (7/9), Lauraceae (8/11), Moraceae (6/7), Melastomataceae (4/4) and Rubiaceae (9/12). In MGPNP the composition is only fairly different: Araliaceae (4/6),Euphorbiaceae (8/13), Lauraceae (9/12), Melastomataceae (5/6), Moraceae (13/22), Myrtaceae (9/11) and Rubiaceae (6/13). At least 23 gall shapes were found in both locations. The most common shape of galls found in MGNP was irregular, while in MHSNP was globular.Galls were mostly (90%) collected from leaf including peduncles and leaf venations. The other parts included twigs, branches, stems, flowers,and fruits. The most common insect found investing galls (i.e. insect gallers) was the midges (54.4%) followed by mites (18.5%), psyllids (11.1%), thrips (6.3%), coccids (1.9%), and aleurodes (1.9%).